2002
DOI: 10.1128/iai.70.10.5882-5886.2002
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Flagella in Nonmotile Enteroinvasive Escherichia coli Isolated from Diarrhea Cases

Abstract: We report that enteroinvasive Escherichia coli (EIEC) serotypes considered to be nonmotile produce an unusually large (77 kDa) flagellin that is assembled into functional flagellum filaments that allow the bacteria to swim in modified motility agar. The EIEC flagellin showed N-terminal identity to most common enterobacterial flagellins, especially those of the E. coli H7 serotype. These data are important in terms of the epidemiology, evolution, and biology of EIEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
2
10
0
1
Order By: Relevance
“…In the present study, the KpBUAP021 strain demonstrated swimming motility in 0.25 % agar notwithstanding that K. pneumoniae has been reported as a non-motile bacterium. Similar results have been reported for E. coli and Shigella (Andrade et al, 2002;Giron, 1995) were flagellar expression has been linked to specific biological micro-environments or different growing conditions in vitro (Andrade et al, 2002;Giron, 1995;Hughes et al, 1993;Schmitt et al, 1994). In our study, only one of 25 K. pneumoniae isolates showed motility as revealed by TEM analysis and Ryu staining (Figs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, the KpBUAP021 strain demonstrated swimming motility in 0.25 % agar notwithstanding that K. pneumoniae has been reported as a non-motile bacterium. Similar results have been reported for E. coli and Shigella (Andrade et al, 2002;Giron, 1995) were flagellar expression has been linked to specific biological micro-environments or different growing conditions in vitro (Andrade et al, 2002;Giron, 1995;Hughes et al, 1993;Schmitt et al, 1994). In our study, only one of 25 K. pneumoniae isolates showed motility as revealed by TEM analysis and Ryu staining (Figs.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported that the percentage of agar is an essential stimulus for swimming motility after cell differentiation. Some bacteria can display swimming motility at agar concentrations as low as 0.3 % or less (Andrade et al, 2002;Giron, 1995;Tercero-Alburo et al, 2014). In the present study, the KpBUAP021 strain demonstrated swimming motility in 0.25 % agar notwithstanding that K. pneumoniae has been reported as a non-motile bacterium.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…Cell-surface TLR-5 recognises flagellin, a structural protein that forms a major portion of flagellar filaments (Ramos et al 2004). Although EIEC are typically immotile, they have been shown to move in modified motility assays conducted at reduced agar concentrations (Andrade et al 2002). Also in accord with our results, Tominaga et al (1994) demonstrated that the flagellin gene is cryptic in the genus Shigella.…”
supporting
confidence: 80%